Individual Differences: From Neurobiological Bases to New Insight on Approach and Avoidance Behavior - Daniela Laricchiuta (Frontiers Research Topics, 2016)
The superordinate division of emotions is distributed along a bipolar dimension of affective valence, from approaching rewarding situations to avoiding punitive situations. Avoiding and approaching behaviors determine the disposition to the primary emotions of fear and attachment and the behavioral responses to the environmental stimuli of danger, novelty and reward. Approach or avoidance behaviors are associated with the brain pathways controlling cognitive and attentional function, reward sensitivity and emotional expression, involving prefrontal cortex, amygdala, striatum and cerebellum. Individual differences in approach and avoidance behavior might be modulated by normal variance in the level of functioning of different neurotransmitter systems, such as dopaminergic, serotoninergic, noradrenergic and endocannabinoid systems as well as many peptides such as corticotropin releasing hormone. These substances act at various central target areas to increase intensity of appetitive or defensive motivation. Physiologically, personality temperaments of approach and avoidance are viewed as instigators of propensity. They produce immediate affective, cognitive and behavioral inclinations in response to stimuli and orient individuals across domains and situations in a consistent fashion. Although the action undoubtedly emerges directly from these temperamental proclivities, ultimate behavioral outcomes are often a function of the integration among goal pursuit, self-regulation, and temperament trait. Defective coping strategies to aversive or rewarding stimuli characterize the patho-physiology of anxiety- and stress-related disorders or compulsive and addiction behaviors, respectively. Individuals with neuropsychiatric symptoms such as depression, suicidal behavior, bipolar mania, schizophrenia, substance use disorders, pathological gambling and anxiety disorders have scores which fall at the extreme tails of the normal distribution for a specific temperamental trait. The present Research Topic on the individual differences in emotional and motivational processing emphasizes the link between neuronal pattern and behavioral expression. The Topic includes experimental and clinical researches addressing the individual differences related to approach and avoidance and their behavioral characterization, structural and neurochemical profiles, synaptic connections, and receptor expressions. Studies are organized in a framework that puts in evidence the phenotypic expression and neurobiological patterns characterizing the individual differences and their biological variance.